2009
DOI: 10.1111/j.1755-0998.2008.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Subspecies‐informative SNP assays for evaluating introgression between native golden trout and introduced rainbow trout

Abstract: We characterize 20 single nucleotide polymorphism assays for evaluating hybridization between native golden trout subspecies (Oncorhynchus mykiss aguabonita and O. m. whitei) and introduced rainbow trout strains. These assays utilize the 5'-nuclease reaction, facilitating high-throughput genotyping of many individuals and making them useful in quantifying and monitoring introgression and potentially applicable to studies of other O. mykiss groups. Minor allele frequency differentials (δq) among native and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The four controlled hybrids of E. camaldulensis × (E. urophylla × E. globulus) showed the anticipated hybrid composition with a predominance of E. camaldulensis genome, although the relative proportions did not match the expectations, especially considering the small proportion of E. globulus contribution, theoretically expected at 25% but observed only at Fig. Following intensive screening efforts, selected SNPs with contrasting allele frequencies among the populations under study have been found and used for assignment tests in admixed humans (Lins et al 2010) and animal (Stephens et al 2009) populations. Each individual is represented as a vertical line partitioned into K colored segments whose length is proportional to the individual coefficients of membership in each of the K inferred clusters that represent the four species of Eucalyptus.…”
Section: Resultsmentioning
confidence: 97%
“…The four controlled hybrids of E. camaldulensis × (E. urophylla × E. globulus) showed the anticipated hybrid composition with a predominance of E. camaldulensis genome, although the relative proportions did not match the expectations, especially considering the small proportion of E. globulus contribution, theoretically expected at 25% but observed only at Fig. Following intensive screening efforts, selected SNPs with contrasting allele frequencies among the populations under study have been found and used for assignment tests in admixed humans (Lins et al 2010) and animal (Stephens et al 2009) populations. Each individual is represented as a vertical line partitioned into K colored segments whose length is proportional to the individual coefficients of membership in each of the K inferred clusters that represent the four species of Eucalyptus.…”
Section: Resultsmentioning
confidence: 97%
“…Among teleost fish species, salmonid researchers have been pioneering in efforts to develop diagnostic SNP assays useful in assessing and managing genetic integrity and measuring impacts of hybridization with non-native, introduced populations (e.g. Stephens et al 2009;Hohenlohe et al 2011;Kalinowski et al 2011;Lamaze et al 2012;Pritchard et al 2012Pritchard et al , 2013Lamer et al 2014). SNP development and application in these studies have generally taken one of two approaches: RNA-seq on pooled samples followed by validation in greater numbers of individual samples (Lamaze et al 2012) or reduced-representation sequencing of individual samples using RAD-seq or GBS approaches (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mexico holds a number of as yet undescribed forms and lineages of O. mykiss (Behnke, 1992(Behnke, , 2002Hendrickson et al, 2002), while no morphological traits exist for identification of Kamchatkan rainbow trout (O. m. mykiss), Little Kern River golden trout (O. m. whitei), Kern River rainbow trout (O. m. gilberti) or Eagle Lake rainbow trout (O. m. aquilarum), though Behnke supports these distinctions for pragmatic reasons. Meanwhile, many molecular genetic studies have attempted to describe relationships among native rainbow trout lineages and have mostly shown agreement with the morphological data (Bagley and Gall, 1998;Stephens et al, 2009;Simmons et al, 2010).…”
Section: Biological and Evolutionary Characteristics Of Rainbow Troutmentioning
confidence: 91%